Should the IMF resort to private credit markets for refinancing? - Anton Konrad (Intereconomics, 1982)
The International Monetary Fund is at present examining the possibility of borrowing on private capital markets in order to meet its growing refinancing needs. Reservations concerning such a step have been voiced in particular by the oil-importing developing countries. Professor Konrad analyses the pros and cons.
Keywords: 330; International Monetary Fund